2013
DOI: 10.1063/1.4795525
|View full text |Cite
|
Sign up to set email alerts
|

In-situ post-annealing technique for improving piezoelectricity and ferroelectricity of Li-doped ZnO thin films prepared by radio frequency magnetron sputtering system

Abstract: Li-doped zinc oxide (L0.03Z0.97O) thin films are deposited onto Pt/Ti/SiO2/Si substrates via the radio frequency magnetron sputtering method. The structure evolution with annealing temperature of the predominantly (002)-oriented Li-doped ZnO (LZO) films after in-situ post-annealing process is determined. The largest values of the piezoelectric coefficient (d33) and the remnant polarization (Pr) (22.85 pm/V and 0.655 μC/cm2, respectively) are obtained for LZO films post-annealed at 600 °C, which can be attribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Full details of the synthesis process are available in a previous study by the present group. 9 LZO films were deposited on Pt/Ti/SiO 2 /Si substrates at room temperature in a 25% oxygen and 75% argon mixed gas atmosphere. The deposition process was performed using a constant RF power of 120 W, a substrate rotation speed of 6 rev/min, and DC-bias voltages in the range of 0 ∼ 25 V. To minimize the effects of experimental errors on the properties of the deposited film, the target and samples were placed in parallel and the target-to-substrate distance was carefully set to 80 mm in every experiment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Full details of the synthesis process are available in a previous study by the present group. 9 LZO films were deposited on Pt/Ti/SiO 2 /Si substrates at room temperature in a 25% oxygen and 75% argon mixed gas atmosphere. The deposition process was performed using a constant RF power of 120 W, a substrate rotation speed of 6 rev/min, and DC-bias voltages in the range of 0 ∼ 25 V. To minimize the effects of experimental errors on the properties of the deposited film, the target and samples were placed in parallel and the target-to-substrate distance was carefully set to 80 mm in every experiment.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that post-annealing up to 600 • C is an effective means of improving the piezoelectric and ferroelectric properties of LZO films for silicon-based electronic devices. 9 However, such an approach cannot be applied for flexible electronic devices since flexible substrates typically have a maximum working temperature of 200 • C. 10 Accordingly, the present study synthesizes 3 at% Li-doped zinc oxide (L 0.03 Z 0.97 O, LZO) thin films on Pt/Ti/SiO 2 /Si substrates using a radio frequency (RF) magnetron sputtering technique with synchronous DC-bias voltages ranging from 0 ∼ 25 V. The effects of the DC voltage on the microstructure, thickness uniformity, piezoelectric and dielectric properties of LZO thin films are systematically explored. It is shown that the proposed technique enables the fabrication of LZO thin films with superior piezoelectric and dielectric properties without the need for post-treatment or annealing processes.…”
mentioning
confidence: 99%
“…Film characterization includes the first positron annihilation spectroscopy (PAS) measurements on oxide thin films to our knowledge, X-ray photoelectron spectroscopy (XPS), X-ray reflectivity (XRR), and capacitancevoltage (C-V) data, supporting the broad applicability of SCS. or Ga 3+ frustrates crystallization (27)(28)(29)(30). XPS oxygen 1s analysis of the O-bonding states in the films (SI Appendix, Fig.…”
Section: Significancementioning
confidence: 99%
“…The target for the RF magnetron sputtering system was synthesized using reagent-grade ZnO and Li 2 CO 3 powders with purities in excess of 99.99%. Full details of the synthesis process are available in a previous study by the present group [10]. LZO films were deposited on Pt/Ti/SiO 2 /Si substrates at room temperature in a 25% oxygen (O 2 , purity: 99.995%) and 75% argon (Ar, purity: 99.995%) mixed gas atmosphere.…”
Section: Methodsmentioning
confidence: 99%